JC virus/human immunodeficiency virus 1 co-infection in the Brazilian Amazonian region - Cayres-Vallinoto, Izaura Maria Vieira; Vallinoto, Antonio Carlos Rosário; Pena, Giselle Priscila dos Anjos; Azevedo, Vânia Nakauth; Machado, Luiz Fernando Almeida; Ishak, Marluísa de Oliveira Guimarães; Ishak, Ricardo (The Brazilian journal of infectious diseases, 2016)
JC virus (JCV) is a member of the Polyomaviridae family and is associated to a severe disease known as progressive multifocal leukoencephalopathy, PML, which is gradually increasing in incidence as an opportunistic infection among AIDS patients. The present study aimed to investigate the occurrence of JCV among HIV-1 carriers including their types and molecular subtypes and the possible association with disease. Urine samples from 66 HIV-1 infected subjects were investigated for the presence of the virus by amplifying VP1 (215bp) and IG (610bp) regions using the polymerase chain reaction. JCV was detected in 32% of the samples. The results confirmed the occurrence of type B (subtype Af2); in addition, another polyomavirus, BKV, was also detected in 1.5% of samples of the HIV-1 infected subjects. Apparently, there was no significant difference between mono- (HIV-1 only) and co-infected (HIV-1/JCV) subjects regarding their TCD4+/TCD8+ lymphocyte counts or HIV-1 plasma viral load. Self admitted seizures, hearing and visual loses were not significantly different between the two groups.